PKM APLIKASI EMAK (ENGLISH AND MATHEMATICS ACQUISITION THROUGH KUMON METHOD) SEBAGAI PROGRAM LITERASI SEKOLAH - Syita Fatih 'Adna; Aprilia Nurul Chasanah; Noor Sahid Kusuma Hadi Manggolo; Dimas Dwi Putra Alamsyah; Diva Maulida; Vina Ariska; Yemmi Pitaloka Bronte Anwar (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2023)
Mathematical and English literacy are skills that students must master in the current era of globalization. Mathematical literacy focuses on numeracy literacy, while English literacy focuses on reading and writing literacy. Based on data, Mathematics literacy and English literacy of SMPIT Ihsanul Fikri students in Magelang City are still relatively low. There are still many teachers who have not found suitable learning methods to apply to improve their students' mathematics and English literacy. The effective application of the Kumon method in learning is still unknown to SMPIT teacher Ihsanul Fikri. Apart from that, mastery of Mathematics literacy and English literacy is also not yet aligned with literacy programs in schools. Thus, Community Partnership Empowerment (PKM) activities were held in the form of training and assistance in creating the EMAK (English and Mathematics Acquisition through Kumon Method) application. The EMAK application uses the Moodle platform so it can be controlled with an admin account, teacher account and student account. PKM activities are carried out through stages of preparation, training, mentoring and evaluation. The training activity involved all Mathematics teachers and English teachers at SMPIT Ihsanul Fikri Magelang City. The posttest results showed an increase in the understanding of the training participants, namely with an average of 82 from the previous 75. Teachers' skills in making quizzes using the EMAK application also increased. Next, FGD activities were carried out to see the successes and obstacles of PKM activities.